PENGEMBANGAN MEDIA PEMBELAJARAN JOBSHEET MATA KULIAH PENGEPASAN BERBASIS PROJECT BASED LEARNING - Rizki Nanda; Rudi Hermawan; Farhan Yadi; Harlin; Wadirin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the validity and practicality of Project Based Learning (PjBL)-based jobsheet learning media in the Packing Practice Course in the Mechanical Engineering Education Study Program. This research is a Research and Development (R&D) research using a 4-D development model. The subject of the study is a UNSRI Mechanical Engineering Education student who is taking a Packing Practice Course. The object of the research is a project-based learning jobsheet for the Fitting Practice Course. The results of the study were obtained that 1) Based on the results of the validation of material experts, an average assessment of 4.26 was obtained with a very valid category, and the results of the validation of media experts obtained an average assessment of 4.4 with a very valid category, thus it can be stated that the jobsheet is very valid in terms of material aspects and media aspects. 2) Based on field trials, it shows that the assessment with an average score of 4.28 indicates that the assessment is very practical. Thus, the project-based learning jobsheets, plates work courses developed in the category are very valid in terms of feasibility and very practical to use.